IMPAIRMENT IN VALUE OF PSAK 7 FINANCIAL ACCOUNTING STANDARDS, CLASSIFICATION OF ACCOUNTING MEASUREMENTS IN HEDGING COMPANIES IN THE BANKING SECTOR DUE TO CORONA VIRUS - Irlan Fery (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
The less difference between SAK and IFRS can provide benefits for stakeholders in commercial banks in Indonesia. Companies that have public accountability, regulators try to make the necessary regulatory infrastructure, especially in capital market transactions, as well as users of financial statement information can use or use financial accounting standards as a guide in improving the quality of information produced in financial statements. value, financial instruments, measurement classification, hedging in banking sector companies due to the corona virus. The results showed that the banking sector experienced a decline in value with the entry of the Corona Virus outbreak which lasted long enough so that the banking sector was depressed which resulted in the value of PSAK 71 changing the condition of banking financial statements so that risk hedges arise from certain risks that can affect profit and loss or comprehensive income. others, in the case of investments in equity instruments that the entity has selected to represent changes in fair value in other comprehensive income.